THE PREVALENCE OF DENTAL RESTORATIONS AND THE STATUS OF TOOTH LOSS WITH CLINICAL AND MICROBIOLOGICAL EFFECTS OF DIFFERENT RESTORATIVE MATERIALS AMONG SAUDI ARABIAN CITIZENS - Tariq Benider Almutairi; Awadh Fahad Almutairi; Nawaf saud Alkhodair; Mohammed abdullah m alfehaid; Hanan Nafea Alharbi; Mansour Saleh AlJarbou; Nawal mammduh alanazi; Dania Bakr Abid; Zaid Saleh Mohammed Al Suleiman (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
In the world's healthiest countries, tooth loss accounts for 2.3% of all cases and is a major cause of disability-adjusted life years (DALYs). Tooth loss is primarily caused by untreated dental caries and has a negative effect on appearance, function, and mental health. The risk of tooth loss in adulthood is increased by developing oral diseases, even with improvements in dental education and conservation. With a 96% success record, dental implants are the ideal option; yet, due to cost and surgical anxiety, awareness of these implants is not universal.This study investigates the patterns of tooth loss in Saudi Arabia, where it is estimated that between 73 and 78% of people may be toothless. Periodontal disease (30–50%) and dental caries (affecting 24-70%) both have a major impact. Trauma is another significant component, especially in younger age groups. Dental restorations, which are between 10 and 20 percent common, are hampered by cultural beliefs, access issues, and budgetary limitations. They are essential for treating tooth loss.In Saudi Arabia, community-based interventions, public health campaigns, and educational initiatives are used to address tooth loss. It is necessary to address the factors that lead to tooth loss, such as inadequate fluoride intake, excessive sugar consumption, poor oral hygiene, limited access to care, and cultural influences. Public health campaigns, educational initiatives, community projects, cost-cutting strategies, and cultural campaigns debunking dental health stereotypes are a few examples of interventions.